2016
DOI: 10.1161/circresaha.115.307599
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Glut1 in Hematopoietic Stem Cells Prevents Myelopoiesis and Enhanced Glucose Flux in Atheromatous Plaques of ApoE −/− Mice

Abstract: Rationale Inflamed atherosclerotic plaques can be visualized by non-invasive PET-CT imaging with 18FDG, a glucose analog but the underlying mechanisms are poorly understood. Objective Here, we directly investigated the role of Glut1-mediated glucose uptake in ApoE−/− mouse model of atherosclerosis. Methods and Results We first show that the enhanced glycolytic flux in atheromatous plaques of ApoE−/− mice was associated with the enhanced metabolic activity of hematopoietic stem and multi-potential progenito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
78
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 56 publications
6
78
0
Order By: Relevance
“…The present observation that low circulating levels of SCF are also associated with an increased cardiovascular mortality adds further support to this notion. Recent studies performed in Apoe-/mice have shown that inhibition of glucose uptake in hematopoietic SC is associated with decreased proliferation of these cells as well as with accelerated atherosclerosis [47]. However, it should be noted that SCF also may have adverse effects on plaque stability through activation of mast cell.…”
Section: Discussionmentioning
confidence: 99%
“…The present observation that low circulating levels of SCF are also associated with an increased cardiovascular mortality adds further support to this notion. Recent studies performed in Apoe-/mice have shown that inhibition of glucose uptake in hematopoietic SC is associated with decreased proliferation of these cells as well as with accelerated atherosclerosis [47]. However, it should be noted that SCF also may have adverse effects on plaque stability through activation of mast cell.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, reducing glycolysis corrects the proinflammatory phenotype of macrophages derived from patients with atherosclerotic coronary artery disease [52]. In addition, a reduction in glycolysis in myeloid cells via GLUT1 deletion inhibits expansion and proliferation of myeloid progenitor cells, leading to a reduction of plaque macrophages in an animal model for atherosclerosis in vivo [73]. …”
Section: Can Trained Immunity Contribute To Atherosclerosis In Diabetmentioning
confidence: 99%
“…These investigators found that the increase in myelopoiesis in diabetic mice was due to increased expression of S100A8/S100A9, which induced GMP proliferation through interaction with the receptor for advanced glycation endproducts (RAGE). Interestingly, Sarrazy et al recently showed that changes in intracellular glucose metabolism in CMPs increased CMP proliferation and monocyte and neutrophil production, and this was regulated by expression of the glucose transporter type 1 (Glut1) 53 . Such data suggest that factors that change metabolism of bone marrow progenitors, such as those linked to hyperlipidemia and hyperglycemia, are key regulators of myelopoiesis.…”
Section: External Factors Controlling Monocyte Developmentmentioning
confidence: 99%